Gestión de venta en la Empresa By Marii del cantón Montalvo en el periodo 2023. - Espín Pelagallo, Juan José (2024)
In summary, the sales management of the company BY MARII in the Montalvo canton during the period 2023 was characterized by a customer-focused approach, obtaining adaptation in the market and the continuous search for service excellence and product offering giving strategies. that contribute to the growth and consolidation of the company in those years, however, it is necessary to carry out a more detailed analysis to evaluate the financial impact of the strategies implemented, which is why the actions taken during this period have strengthened the competitive position of the company in the market. local market. The company BY MARII carried out a local market analysis to identify trends, consumer preferences and local competition, which provides valuable information to adapt its product and service offerings to the needs of the market, which allowed BY MARII to personalize its products. sales and marketing strategies for each of the customer segments thus increasing the effectiveness of their commercial efforts by implementing loyalty programs offering exceptional customer service by constantly seeking offers to improve their offering and purchasing experience. It kept abreast of the latest trends and market demands and regularly introduced new products and services to satisfy the needs that customers could observe. Constant innovation helped maintain customer interest, managing to identify the company from the competition. , the implementation of customer-centered policies has given an increase in the customer satisfaction index, reporting a more positive experience and they are more satisfied with the products and service offered by the company.